Empowering Prospective Biology Teachers: Implementing UDL-Integrated Digital Competencies in Invertebrate Taxonomy at Cenderawasih University - Nurbaya Nurbaya (Jurnal Penelitian Pendidikan IPA, 2026)
This quasi-experimental pretest-posttest non-equivalent control group study examined the effectiveness of Universal Design for Learning (UDL) integrated with digital competence in improving invertebrate taxonomy learning among third-semester Biology Education students at FKIP Cenderawasih University. Participants included 54 students from two classes: the experimental (n=27) receiving 6-week UDL-digital intervention and the control group (n=27) following conventional PowerPoint lectures. The intervention applied UDL principles: Multiple Means of Representation via e-modules, 3D animations, and infographics; Action/Expression through digital portfolios, videos, and quizzes; and Engagement via LMS feedback.  Quantitative data were collected through tests of conceptual mastery, digital competence assessments, and classroom engagement observations, while qualitative data were obtained from student questionnaires and semi-structured interviews. The findings indicate that students exposed to the UDL-digital approach achieved higher conceptual understanding, demonstrated stronger digital competence, and showed greater engagement than those in the control group. Qualitative results supported these outcomes, revealing that multimodal access facilitated understanding of complex taxonomy concepts, flexible digital expression enhanced self-efficacy, and gamified learning environments increased intrinsic motivation, particularly when learning was contextualized using local biodiversity. Overall, the study confirms the potential of UDL integrated with digital competence as an effective and inclusive pedagogical framework for STEM teacher education. The findings suggest that UDL-digital learning designs are particularly relevant for resource-constrained higher education contexts and can contribute to preparing future biology teachers who are both pedagogically adaptive and digitally competent.